THE EFFECT OF ERGONOMIC GYMNASTICS ON HYPERTENSION RISK OF ELDERLY COMMUNITIES - Putra, Eko Perdana; Lassie, Naima; Primawati, Irma; Maribeth, Annisa Lidra (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
This research looked to investigate if ergonomic exercise had any impact on the blood pressure values of elderly people with hypertension. Pre-experimental research design is used in this quantitative study type. Data collection was carried out offline for respondents using a sphygmomanometer and observation sheets. The Wilcoxon test was employed for data analysis. The findings revealed that the average difference in systole before and after ergonomic exercise was 20.96 mmHg, and the average difference in diastole before and after ergonomic exercise was 14.56 mmHg. The results of ergonomic exercise interventions can be evident in the changes in systolic and diastolic blood pressure measurements. After conducting the statistical analysis, it was discovered that the p value for systolic blood pressure was 0.000 with 25 respondents. This means that p < ? (0.000 < 0.05) indicates that Ho is rejected and Ha is approved. It may be concluded that ergonomic exercise has a substantial effect on the blood pressure values of elderly who have high blood pressure (hypertension).